Role Profit Growth Moderates Environmental Costsregarding ISR Disclosures (Comparative Study between Islamic and Conventional Banks for the 2016-2020 Period) - Siti Baroroh; Chairun Nissa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to analyze the effect of profit growth moderating environmental costs on ISR, Good Corporate Governance (audit committee, Board of Directors and Sharia Supervisory Board) and Leverage on Islamic Social Reporting moderated by Environmental Costs and to compare these variables between Conventional Banks and Islamic Banks. Data used in this study is secondary data in the form of financial reports of Islamic banks and conventional banks listed on the IDX during the 2016-2020 period. The number of banks during the study period was 11 Islamic Banks and 10 Conventional Banks with a total of 103 samples. The analysis used in this study is a multiple regression analysis model. The findings from the research results show that the Sharia Supervisory Board variable has no effect on Islamic Social Reporting.